Evaluating Secondary Students' Scientific Reasoning in Genetics Using a Two-Tier Diagnostic Instrument - Tsui, Chi-Yan; Treagust, David (Routledge, 2010)
While genetics has remained as one key topic in school science, it continues to be conceptually and linguistically difficult for students with the concomitant debates as to what should be taught in the age of biotechnology. This article documents the development and implementation of a two-tier multiple-choice instrument for diagnosing grades 10 and 12 students’ understanding of genetics in terms of reasoning. The pretest and posttest forms of the diagnostic instrument were used alongside other methods in evaluating students’ understanding of genetics in a case-based qualitative study on teaching and learning with multiple representations in three Western Australian secondary schools. Previous studies have shown that a two-tier diagnostic instrument is useful in probing students’ understanding or misunderstanding of scientific concepts and ideas. The diagnostic instrument in this study was designed and then progressively refined, improved, and implemented to evaluate student understanding of genetics in three case schools. The final version of the instrument had Cronbach’s alpha reliability of 0.75 and 0.64, respectively, for its pretest and the posttest forms when it was administered to a group of grade 12 students (n = 17). This two-tier diagnostic instrument complemented other qualitative data collection methods in this research in generating a more holistic picture of student conceptual learning of genetics in terms of scientific reasoning. Implications of the findings of this study using the diagnostic instrument are discussed.